A comparative evaluation of behavioral security motives: Protection, intrinsic, and identity motivations. Issue 128 (May 2023) - Ogbanufe, Obi; Ge, Ling
Abstract: This study examines the contrast between three motivation theories (identity, protection, and intrinsic) and their impact on two forms of security behaviors (in-role and extra-role). The information security literature has informed much of our understanding of how individuals are motivated to perform security behaviors, with a predominant focus on the Protection Motivation and Intrinsic Motivation theories. We draw from recent insights from the Identity Theory and its explanation of behaviors in the workplace to compare motivations toward in-role and extra-role security behaviors. Whereas identity is influential in positively motivating in-role and extra-role behaviors, intrinsic motivation does not influence in-role behaviors, and protection motivation reduces extra-role behaviors. These results provide insights on the role that identity plays as a capable motivation with implications for research and practice.